AN ANALYSIS OF THE UNDERSTANDING OF TAX REGULATIONS, TAXPAYER AWARENESS, AND TAX SOCIALIZATION IN INFLUENCING MSME TAX COMPLIANCE (a case study of micro, small, and medium enterprises in West Denpasar, Indonesia) - Theresia Ni Made Evangela Berliana; Ni Luh Supadmi (Adisam Publisher, 2025)
The government has demonstrated significant efforts to improve taxpayer compliance. However, the compliance level of MSME taxpayers remains relatively low despite the increasing number of taxpayers and tax revenue. This study aims to analyze the influence of tax regulation understanding, taxpayer awareness, and tax socialization on MSME taxpayer compliance in the West Denpasar area. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents selected using purposive sampling. The data were analyzed using multiple linear regression. The results show that both tax regulation understanding and taxpayer awareness have a positive and significant effect on MSME taxpayer compliance. Tax socialization also has a positive and significant influence, although its effectiveness depends on the media and delivery methods used. These findings emphasize the importance of continuous education and outreach efforts to enhance tax compliance in the MSME sector. This study is expected to contribute to tax authorities in formulating strategies to improve taxpayer compliance through integrated internal and external approaches.